An efficient deep learning approach for 3D face detection using multiple angular 2D images - Rafsan, Nayeem; Nayeem, Hasibul Hoque; Dad, Hamed Efaz Md. Elahi; Yen, Afzal Hossain (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.